SOLVE:

1) 2(x+5)-(x-6)=3(x+7)-3

2) 5(x-13)=10x-(2x+5)

3) x-[2x - 5x-1 /3]=x-1 /3 + 1/2

by sherinmohan

last one take the LCM of 3,3,2

Log in to add a comment

SOLVE:

1) 2(x+5)-(x-6)=3(x+7)-3

2) 5(x-13)=10x-(2x+5)

3) x-[2x - 5x-1 /3]=x-1 /3 + 1/2

by sherinmohan

last one take the LCM of 3,3,2

Log in to add a comment

The Brainliest Answer!

2x+10-x+6=3x+21-3

2x-x-3x=21-3-16

-2x=2

x=2/-2

x=-1

2.5(x-13)=10x-(2x+5)

5x-65=10x-2x-5

5x-8x=-5+65

-3x=60

x=60/-3

x=-20

3.x-[2x - 5x-1 /3]=x-1 /3 + 1/2

x-2x+5x+1/3=x-1/3+1/2

taking lcm

by cross multiply

-18x+6=18x+3

-18x-18x=3-6

-36x=-3

x=-3/-36

x=1/12